Norway : 2011 Article IV Consultation: Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Norway. (IMF Staff Country Reports; Country Report ;, 2012)
Norway's near-term macroeconomic priority is to reduce risks arising from high-household debt by tightening macroprudential standards for mortgage lending while undertaking tax reforms to gradually reduce incentives for excessive leverage. Creating a stronger institutional framework for acroprudential policy would also assist risk mitigation in the future. With the output gap closing, fiscal tightening is needed over the medium term in the central scenario to rebuild precautionary buffers and ensure that fiscal guidelines are met on average over the cycle.